2016
DOI: 10.18632/oncotarget.14212
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome nondisjunction during bipolar mitoses of binucleated intermediates promote aneuploidy formation along with multipolar mitoses rather than chromosome loss in micronuclei induced by asbestos

Abstract: Asbestos is a well-known occupational carcinogen that can cause aneuploidy during the early stages of neoplastic development. To explore the origins of asbestos-induced aneuploidy, we performed long-term live-cell imaging followed by fluorescence in situ hybridization of chromosomes 8 and 12 in human bronchial epithelial (HBEC) and mesothelial (MeT5A) cells. We demonstrate that asbestos induces aneuploidy via binucleated intermediates resulting from cytokinesis failure. On the one hand, asbestos increases chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Asbestos-induced chromosomal instability and consequent aneuploidy, a hallmark of cancer cells, has been observed in various types of in vitro cultured mammalian cells [3239]. Recently, Zhang et al [40] has demonstrated that aneuploid cells are generated from binucleated cells through multipolar mitosis or bipolar mitosis with chromosome nondisjunction. Changes in the copy numbers of chromosomes or large chromosomal regions in aneuploid cells significantly alter the expression of several hundreds of genes.…”
Section: Resultsmentioning
confidence: 99%
“…Asbestos-induced chromosomal instability and consequent aneuploidy, a hallmark of cancer cells, has been observed in various types of in vitro cultured mammalian cells [3239]. Recently, Zhang et al [40] has demonstrated that aneuploid cells are generated from binucleated cells through multipolar mitosis or bipolar mitosis with chromosome nondisjunction. Changes in the copy numbers of chromosomes or large chromosomal regions in aneuploid cells significantly alter the expression of several hundreds of genes.…”
Section: Resultsmentioning
confidence: 99%
“…Since inactivation of the proteasome by RNAi or use of inhibitors produces aberrant nuclei in C. elegans germline [ 43 , 50 ] and BAP1 has a regulatory function on ubiquitination of histones [ 55 ], genome instability would be the “hallmark of cancer” behind the BAP1 alterations. Interestingly, although the specific mechanism of carcinogenesis induced by asbestos in MPM is still unclear, it has been proposed that asbestos causes genome instability [ 56 ] and chromosomal segregation defects [ 57 ]. Given the limited effective therapeutic intervention in MPM [ 58 ], and that about 50% of cases of MPM present alteration in BAP1 [ 59 ], the development of animal models such as the one presented here would open new venues to detect vulnerabilities of cells with mutations in BAP1 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to all the other above-mentioned metabolic readjustments that TNT-linked cells may have to deal with, the intrusion and influx of cytoplasmic material from a non-dividing cell could definitely affect the entire geometry of a mitotic cell with its otherwise orderly aligned chromosomes and its highly vulnerable intricate spindle scaffold (Ong and Torres, 2020). Depending on the site of the TNTs intrusion relative to the cell equator and depending on the magnitude of its exerted effect, such an interference could displace and move the metaphase plate with its accurately arranged chromatids and, consequently, also reposition the cell's division plane and cytokinetic cleavage furrow in an analogous but much more subtle fashion as, for instance, was shown for asbestos fibers (Zhang et al, 2017;Ong and Torres, 2020). Together with the possible direct disruption of spindle tubules, such developments could ultimately lead to a maldistribution and irregular segregation of chromosomes into daughter cells, which are only able to survive and prosper in case they receive a proper fitting set of compatible chromosomes (Figure 4).…”
Section: Tunneling Nanotubesmentioning
confidence: 92%